Success factor in the implementation of TQM in public service agencies - Muhamad, Mazanah; Kamis, Mazalan (Universiti Utara Malaysia, 2003)
This study aims specifically to determine factors contributing to the success of TQM implementation in selected goverment agencies. A total of six goverment agencies nominated for the Prime Minister Quality Awards were studied. A qualitative method was employed in which data were collected through unstructured interviews. Documents pertaining to the implementation of TQM in the respective agencies were also used as a source of data. Data were analyzed inductively by developing categories, coding, and categorization. The findings reveal that factors contributing to the success of TQM implementation were: (1) good leadership, (2) involvement and commitment of all level of staf, (3) meeting customer satisfaction, (4) reward and recognition,(5) teamwork, (6)awareness, and (7) organizational climates. Although, TQM implementation in these selected government agencies were in line with the method suggested in the literature, there appear to be some uniqueness in the scope of training and the concerns of the organization towards their staf. The emphases on religious values and concerns for culture have played a pivotal role in shaping the implementation and the success of TQM in public service agencies.